Cranial MR in Wilson disease: abnormal white matter in extrapyramidal and pyramidal tracts. - van Wassenaer-van Hall, H N; van den Heuvel, A G; Jansen, G H; Hoogenraad, T U; Mali, W P (American Journal of Neuroradiology, 1995)
PURPOSE To describe abnormal white matter in the brain on MR in Wilson disease and to compare with anatomic location of white matter tracts. METHODS Forty-six patients with Wilson disease were examined. Axial T1-weighted inversion-recovery, axial T2-weighted spin-echo, and coronal T2*-weighted gradient-echo MR images were performed. Imaging studies were compared with clinical data. RESULTS Seventeen patients showed abnormalities in the region coinciding with the following white matter tracts: corticospinal tract (24%, n = 11), dentatorubrothalamic tract (24%, n = 11), and pontocerebellar tract (17%, n = 8). CONCLUSION Abnormal extrapyramidal and pyramidal white matter tracts are part of the neuroimaging spectrum of Wilson disease. No significant correlation was found with neurologic groups and individual white matter tracts affected.